2017
DOI: 10.1158/1055-9965.epi-16-0786
|View full text |Cite
|
Sign up to set email alerts
|

Do Men and Women Need to Be Screened Differently with Fecal Immunochemical Testing? A Cost-Effectiveness Analysis

Abstract: Several studies suggest that test characteristics for the fecal immunochemical test (FIT) differ by gender, triggering a debate on whether men and women should be screened differently. We used the microsimulation model MISCAN-Colon to evaluate whether screening stratified by gender is cost-effective. We estimated gender-specific FIT characteristics based on first-round positivity and detection rates observed in a FIT screening pilot (CORERO-1). Subsequently, we used the model to estimate harms, benefits, and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…However, a decision analysis has shown that risk stratification by gender is currently not effective. 19 We were unable to demonstrate that FIT sensitivity differed by age. This is contrary to other findings suggesting a different sensitivity by age, although the studies presented conflicting results.…”
Section: Discussionmentioning
confidence: 70%
“…However, a decision analysis has shown that risk stratification by gender is currently not effective. 19 We were unable to demonstrate that FIT sensitivity differed by age. This is contrary to other findings suggesting a different sensitivity by age, although the studies presented conflicting results.…”
Section: Discussionmentioning
confidence: 70%
“…Utilization of FIT as a screening biomarker may also generate significant financial savings. According to an economic analysis by Palimaka et al, the average cost of a capsule endoscopy is approximately $950 CAD (approximately €633 at 2015 exchange rate) 20 , while the cost of FIT stands at approximately €20 to €30 21 . Applying these data to our cohort, use of FIT > 45 ug Hb/g as a screening tool could have saved our department approximately €19,456 over the course of the study period, with four false-negative cases as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have supported this finding [97,100,101], and thus, the effect on screening results of different cut-off levels for men and women is not yet clarified. In fact, in the Netherlands, it was shown that the current model was recommended based on a study comparing findings in men and women [102].…”
Section: Gender and Age Differences In Crc Screeningmentioning
confidence: 99%